Marketing Strategy Analysis in Increasing Quantity Hypnotherapy Training Participants on Indonesian Hypnosis Center (LKP IHC) Courses and Training Institute in Mataram City Province West Nusa Tenggara - Toha Afifi; Muhammad Fauzan Azhmy; Ezzah Nahrisah; Annisha Suvero Suyar (Budapest International Research and Critics University, 2022)
This study aims to find out how the marketing strategy in accordance for applied to LKP English Hypnosis Center (IHC) in increasing the number of trainees in time pandemic COVID-19 based on an analysis SWOT (Strengths, Weaknesses, Threats, Opportunity). In this study, the author uses a qualitative method with the technique of triangulation data. Technique collection data used is method observation, Interview, documentation, and questionnaire. Technique analysis data used are SWOT analysis, IFAS matrix, EFAS matrix, SWOT diagram, and the SWOT matrix. Furthermore, based on the results of the analysis using the IFAS matrix, EFAS matrix, SWOT diagram, and SWOT matrix, then it can be it is known that the LKP Indonesian Hypnosis Center (IHC) is running strategy SO (Strength- Opportunity) is a strategy where the organization uses their strengths and opportunities to run their business. With thereby LKP English Hypnosis Center (IHC) should concentrate maintain and increase program training which varies according to the needs of the community with 3 main points, namely: (1) Utilization of social media with a maximum for promotion sales. (2) Use of online seminars to expand market segments and increase the quantity of loyal participant training. (3) Development program training in accordance needs as adjustment self so that effort permanent endure in time pandemic.